The Transpacific Travel from India to Canada in Life of Pi by Yann Martel and Its Link to Transculturality and Transdisciplinarity - Imbert, Patrick (Review of International American Studies, 2014)
Patrick Imbert Univeristy of Ottawa Canada The goal is to see how the transpacific travel of the immigrant Piscine from India to Canada in the best seller and Booker Prize novel Life of Pi allows us to revisit the dynamic of exclusion, and the idea of nation and place as well as to recognize alterity in perspectives emphasizing more transculturalism than multiculturalism. This anthropo-thematic analysis will lead us to a theoretical perspective based upon the comparison between trans-multi-interdisciplinary and trans-multi-intercultural perspectives and to establish links between the trans, the multi and the inter in the context of the legitimacy of symbolic and geographic displacements and of multiple encounters as they are linked to the Americas.